THE CORRELATION OF ANXIETY IN DEALING WITH OBJECTIVE STUDENT ORAL CASE ANALYSIS (OSOCA) EXAMINATION ON THE CASE OF FUNCTIONAL DYSPEPSIA IN THE FIRST SEMESTER MEDICAL STUDENTS - Juharny Eka Sackbani; Thysa Thysmelia Affandi; Defa Nur Rahamtunnisaa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Anxiety is a psychological reaction caused by a variety of factors, one of which is when a student has an examination. Objective Student Oral Case Analysis (OSOCA) is one of the examinations that is a main indicator of learning achievements of medical students in the faculty of medicine. Anxiety can cause a variety of other health problems, such as functional dyspepsia. This study aims to analyze the correlation of anxiety in dealing with objective student oral case analysis (OSOCA) examination and the cases of functional dyspepsia in the first semester medical students.Methods: This research was an observational study with a cross-sectional design. A total of 132 medical students were recruited as respondents. Zung Self-rating Anxiety Scale (ZSAS) questionnaire was used to asses anxiety and a questionnaire based on Rome III criteria that was previously validated was used to measure functional dyspepsia. The data were analyzed using Spearman correlation test and prevalence ratio was determined.Results: The result based on Spearman correlation test showed significant weak positive correlation between anxiety and functional dyspepsia with r=0,295 (p=0,001). Student with moderate anxiety scales have 5 times greater risk of functional dyspepsia than student who have mild anxiety scales (PR=5,300).Conclusion: There is a significant correlation between anxiety and functional dyspepsia. Students with moderate anxiety scales have 5 times greater risk of functional dyspepsia than students who have mild anxiety scales.